The Design of Portable Battery Charging Devices Using Motorcycle Wheel Round - Arlenny (International Journal of Electrical, Energy and Power System Engineering, 2019)
This research aims to the development of reader equipment as well as control the load limitation of electric power using the Atmega 8535 microcontroller. In the development of equipment for reading and controlling electrical energy consumptions, the modified KWH (KiloWatt Hour) meter was used by placing the optocoupler sensor as the enumerator indicator of the electric power consumption on the disc. Atmega 8535 microcontroller was used to control and limitation of the electric power consumption. In this research, the measuring and control system was developed to record the amount of electrical power load used, and it can be used as an alternative to the current divider for the achievement of the efficiency of practical electrical energy consumption. The results of the measurement comparison between the measured load and the output load tended to be stable with an average percentage error of 6.3%, and it was still below the optimum threshold value of the error factor, which around 10%. Therefore, the results of testing developed equipment KWH digital meter using Atmega 8535 microcontroller that was produced a good performance.